Thermal inactivation of polyphenoloxidase and peroxidase in Jubileu clingstone peach and yeast isolated from its spoiled puree - Lopes,Andréa Menezes (2014)
The thermal inactivation of yeast isolated from spoiled Jubileu peach puree and that of polyphenoloxidase (PPO) and peroxidase (POD) in cv. Jubileu, which is widely cultivated in southern Rio Grande do Sul state, Brazil, were studied. PPO and POD were extracted using the protein powder method and submitted to partial purification by precipitation followed by dialysis. The enzymatic activity was determined measuring the increase in absorbance at 420 nm for PPO and 470 nm for POD. The yeast used in this investigation was isolated from spoiled Jubileu peach puree at 22 °Brix, with total initial microbial count of 22 × 10² UFCmL- 1. Stock cultures were maintained on potato dextrose agar (PDA) slants at 4 °C and pH 5 for later use for microbial growth. In all cases, kinetic analysis of the results suggests that the thermal inactivation was well described by a first-order kinetic model, and the temperature dependence was significantly represented by the Arrhenius law. Both enzymes were affected by heat denaturation, and PPO was more thermostable. PPO was also more thermosTable than the yeast isolated from peach puree. The D60-values were 1.53 and 1.87 min for PPO and yeast isolated from spoiled Jubileu peach puree, respectively.